Department of USSR history at the Kabardian State Pedagogical Institute (LATE 1940S – 1957): main directions of scientific research - Elena G. Muratova; Yulia A. Ortanova (Кавказология, 2022)
Based on archival documents and historiographic sources, the article defines the main directions of scientific research of teachers who worked at the Department of History of the USSR of the Kabardian Pedagogical Institute in the late 1940s–1957. The facts of the scientific biography of A.I. Pershits, V.A. Ryumin, V.P. Krikunov, I.F. Muzhev, A.I. Shchegolev, M.N. Krivushin, T.I. Agapova, R.H. Gugov, T.Kh. Kumykov related to this stage of their scientific and pedagogical career are presented. The article shows that one of the priority areas of scientific activity among the employees of the Department of USSR History in the period under review was the development of the key problems in the history of Kabarda. The article was written for the ninetieth anniversary of the Kabardino-Balkarian State University and is dedicated to the teachers who stood at the origins of historical science and historical education in the republic.